Measurement of the cross-section for producing a W boson in association with a single top quark in pp collisions at √s=13 TeV with ATLAS - Onofre, A. (2018)
The inclusive cross-section for the associated production of a W boson and top quark is measured using data from proton-proton collisions at s√=13 TeV. The dataset corresponds to an integrated luminosity of 3.2 fb−1, and was collected in 2015 by the ATLAS detector at the Large Hadron Collider at CERN. Events are selected requiring two opposite sign isolated leptons and at least one jet; they are separated into signal and control regions based on their jet multiplicity and the number of jets that are identified as containing b hadrons. The W t signal is then separated from the tt¯ background using boosted decision tree discriminants in two regions. The cross-section is extracted by fitting templates to the data distributions, and is measured to be σ W t  = 94 ± 10(stat.) − 22 + 28 (syst.) ± 2(lumi.) pb. The measured value is in good agreement with the SM prediction of σtheory = 71.7±1.8 (scale)± 3.4 (PDF) pb [1].